Reprogramming Hairy Root Cultures: A Synthetic Biology Framework for Precision Metabolite Biosynthesis - Chang Liu; Naveed Ahmad; Ye Tao; Hamad Hussain; Yue Chang; Abdul Wakeel Umar; Xiuming Liu (Plants, 2025)
Hairy root cultures induced by Agrobacterium rhizogenes (Rhizobium rhizogenes) provide a sustainable approach to meet the growing demand for economically valuable plant-derived compounds in the face of depleting natural resources. These cultures exhibit rapid, hormone-independent growth and genetic stability, making them viable for producing bioactive compounds, plant-specialized metabolites, and recombinant proteins. However, challenges remain in optimizing large-scale production, improving bioreactor efficiency, and enhancing metabolite synthesis across different plant species. This review addresses these challenges by exploring the mechanisms behind the induction of hairy root cultures, their applications in genetic and metabolic engineering, and their potential in environmental remediation. The review further highlights recent advances in biotechnology and illustrates how the hairy root system can sustainably meet industrial, pharmaceutical, and agricultural needs. In addition, by pointing out essential research areas such as optimizing culture conditions, increasing metabolite yields, and scaling up production, this work strengthens the significance of hairy root cultures in meeting the demand for high-value products while ensuring sustainable resource utilization. In particular, the integration of hairy root systems with advanced genomic tools such as transcriptomics and CRISPR technology holds immense potential for accelerating pathway-specific metabolic engineering, enhancing biosynthetic flux, and expanding their applications in sustainable agriculture and pharmaceutical innovation. This convergence is expected to drive substantial economic value by optimizing the production of high-value bioactive compounds, improving crop resilience, and facilitating precision medicine. Future work involving systems and synthetic biology will be instrumental in unlocking novel functions and ensuring broader deployment of hairy root cultures across industrial biotechnological platforms.